Eu < 2 + >-doped aluminoborate-based luminescent material as well as preparation method and application thereof

CN119529825APending Publication Date: 2025-02-28CHANGSHU INSTITUTE OF TECHNOLOGY +1
0 Cites 0 Cited by

Patent Information

Application Number
CN202411726469.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

Smart Images

  • Figure CN119529825A_ABST
    Figure CN119529825A_ABST
Patent Text Reader

Abstract

The invention discloses an Eu < 2 + >-doped aluminoborate-based luminescent material as well as a preparation method and application thereof, and belongs to the technical field of luminescent materials. The chemical formula of the material is Ba3GaAl3B4O15: 3xEu < 2 + >, x is the mole number of Ba < 2 + > substituted by Eu < 2 + >, and x is more than or equal to 0.01 and less than or equal to 0.07. The preparation method comprises the following steps: weighing compound raw materials containing various cationic elements according to the stoichiometric ratio of the chemical formula, grinding and mixing, and pre-sintering for the first time at 500-950 DEG C in an air atmosphere for 3-10 hours; grinding the pre-sintered sample again, calcining for 5-15 hours for the second time at 950-1150 DEG C in a reducing atmosphere, and cooling to room temperature along with the furnace to prepare a precursor sintered compound; and then the compound is subjected to step-by-step continuous annealing, and the procedure is as follows: in a reducing atmosphere, the temperature is raised to 550-750 DEG C from the room temperature, sintering is performed for 3-5 hours at the constant temperature, then the temperature is raised to 750-950 DEG C, sintering is performed for 3-8 hours at the constant temperature, finally the temperature is raised to 950-1050 DEG C, sintering is performed for 3-8 hours at the constant temperature, and the final product Ba3GaAl3B4O15: 3xEu < 2 + > is obtained by furnace cooling to the room temperature. The post-annealing treatment in the preparation method enables stubborn residual Eu < 3 + > in the material to be completely reduced into Eu < 2 + > ions. The material can be effectively excited by light with ultraviolet and near ultraviolet wavelengths, emits cyan fluorescent powder, and is wide in emission bandwidth, high in luminous intensity and good in thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials and specifically relates to a Eu 2+ Doped boroaluminate-based luminescent material, preparation method and application thereof. Background Art

[0002] Rare earth ion activated phosphors have been widely studied for applications in different technological fields. Among these studies, europium ions (Eu) are one of the most common activators, which have two valence states:

[0003] Eu 3+ and Eu 2+ , their luminescence is completely different. 3+ From 5 D0 to 7 F J (J=0,1,2,3,4) The characteristic sharp spectral lines of forbidden transitions become the red luminescence center. 2+ The spectrum always shows the 6 5d 1 To 4f 7 Broadband emission of the transition is allowed, and covers the emission from ultraviolet wavelengths to infrared wavelengths. 2+ The development and application of activated luminescent materials have received more extensive attention.

[0004] Usually in the process of preparing luminescent materials, no chemical reagents contain Eu 2+ . Used to prepare Eu 2+ The raw chemical for the activation material contains only Eu 3+ ions. Therefore, in the preparation of Eu 2+ When activating the luminescent material, it is basically to put Eu 3+ The mixed raw materials of Eu ions are heated in a reducing atmosphere. However, for some matrix materials, no matter how long or how long they are calcined in a reducing atmosphere, the raw materials 3+ The ion cannot be completely reduced to Eu 2+ , there must be residual Eu 3+ On the one hand, this is related to the structure of the matrix. On the other hand, it may also be related to the occurrence of 2+ To Eu 3+ Studies have shown that the residual Eu 3+ It may be the cause of Eu 2+ An important factor in luminescence quenching.

[0005] This research patent discloses a new type of Eu 2+ Activated boroaluminate-based Ba3GaAl3B4O 15 Luminescent material, preparation method, and Eu2+ In particular, a step-by-step post-annealing method is disclosed, which gradually transforms the microscopic defects of the matrix material at different temperatures and enables the induced new defects to be fixed in the matrix, which can effectively achieve Ba3GaAl3B4O 15 Stubborn Eu residue in the matrix 3+ Completely reduced to Eu 2+ Ions. The material can be effectively excited by ultraviolet and near-ultraviolet wavelengths of light and emit cyan phosphors with wide emission bandwidth, high luminous intensity and good thermal stability. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the existing luminescent materials, and provide a Eu 2+ Doped boroaluminate-based luminescent material, preparation method and application thereof.

[0007] According to a first aspect of the present invention, the present invention provides a Eu 2+ Doped boroaluminate-based luminescent material, the chemical formula of the luminescent material is Ba3GaAl3B4O 15 :3xEu 2+ , x is Eu 2+ Replace Ba 2+ Ion mole number, and 0.01≤x≤0.07, unsubstituted Ba in the chemical formula 2+ and Eu 2+ The total number of moles is 3.

[0008] Preferably, the Eu 2+ The doped boroaluminate-based luminescent material can emit cyan light of 515-525 nanometers under the excitation of light in the ultraviolet-near ultraviolet band.

[0009] Preferably, x is 0.01, 0.03, 0.05 and 0.07.

[0010] According to a second aspect of the present invention, the present invention provides a Eu 2+ A method for doping a boroaluminate-based luminescent material, comprising the steps of:

[0011] Step (1): According to the chemical formula Ba3GaAl3B4O 15 :3xEu 2+ (x is Eu 2+ Replace Ba 2+ ion mole number, 0.01≤x≤0.07), weighing respectively: a compound containing barium ions, a compound containing gallium ions, a compound containing aluminum ions, a compound containing boron ions, and a compound containing europium ions, grinding and mixing the weighed compounds to obtain an initial mixture;

[0012] The mixture is pre-calcined for the first time in an air atmosphere at a temperature of 500°C to 950°C for a time of 3 to 10 hours; cooled naturally to room temperature, and ground evenly;

[0013] The mixture pre-sintered for the first time is calcined for the second time in a reducing atmosphere at a calcination temperature of 950°C to 1050°C for a pre-calcination time of 5 to 15 hours, cooled naturally to room temperature, and ground evenly to obtain a precursor sintered compound;

[0014] Step (2): The precursor sintered compound obtained in step (1) is subjected to post-annealing treatment in a reducing atmosphere, the temperature is gradually increased in stages and maintained for a certain period of time, and then cooled to room temperature to obtain Eu 2+ Doped boroaluminate-based luminescent material; the stepwise heating refers to a temperature of 400-1200°C, and the holding time refers to 0.5-24h. The stepwise heating and holding time calcination is preferably, firstly, the temperature is raised from room temperature to 550-750°C and sintered at the constant temperature for 3-5 hours, then the temperature is raised to 750-950°C and sintered at the constant temperature for 3-8 hours, and finally the temperature is raised to 950-1050°C and sintered at the constant temperature for 3-8 hours, and then cooled to room temperature with the furnace to obtain the final product Eu 2+ Doped boroaluminate-based luminescent materials Ba3GaAl3B4O 15 :3xEu 2+ .

[0015] Preferably, the barium ion compound is one of barium oxide and barium carbonate.

[0016] Preferably, the gallium-containing ion Ga 3+ The compound is gallium oxide.

[0017] Preferably, the compound containing aluminum ions is one of aluminum oxide and aluminum hydroxide.

[0018] Preferably, the compound containing boron ions is one of boron trioxide and boric acid.

[0019] Preferably, the compound containing europium ions is europium oxide.

[0020] Preferably, the reducing atmosphere is one of the following three atmospheres, or any of them:

[0021] combination:

[0022] (1) Hydrogen, or a mixture of hydrogen and nitrogen in a volume ratio of 1:0.2 to 85;

[0023] (2) Carbon monoxide gas;

[0024] (3) Gas produced by the combustion of carbon particles or various activated carbons in air.

[0025] Preferably, in the post-annealing procedure in step (2), the annealing in a reducing atmosphere requires at least two stages with different temperatures and is completed continuously in a single procedure.

[0026] According to a third aspect of the present invention, the present invention provides a Eu 2+ The doped boroaluminate-based luminescent material is used in luminescent and display devices based on ultraviolet and near-ultraviolet light excitation.

[0027] The present disclosure proposes a Eu 2+ The doped boroaluminate-based luminescent material, preparation method and application thereof have the following beneficial effects compared with the prior art:

[0028] First, in the preparation method disclosed in the present application, the step-by-step continuous post-annealing in a reducing atmosphere gradually transforms the microscopic defects in the matrix, so that the new defects are gradually fixed in the matrix, and the stubborn residual Eu in the matrix is ​​completely realized. 3+ Completely reduced to Eu 2+ ion.

[0029] Second, in the traditional Eu 2+ In the preparation method of activating the luminescent material, the residual Eu 3+ It may be the cause of Eu 2+ An important factor in luminescence quenching. A small amount of residual Eu 3+ The influence on luminescence is relatively large, which can greatly reduce the efficiency of luminescence and thermal stability, and also affect the stability of chromaticity. Therefore, compared with the traditional preparation method, the preparation method of this patent obtains Eu 2+ The activated luminescence has high luminescence intensity and good thermal stability.

[0030] Third, the luminescent material prepared by the technical solution of the present invention has little quenching of luminescence at high temperature and a small shift of the main peak of luminescence at high temperature, thus maintaining the stability of chromaticity, which is conducive to the preparation of high-power luminescent and display devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The XRD diffraction patterns of the samples prepared in Examples 1, 2, 3, and 4 of the present disclosure are compared with the X-ray diffraction standard card PDF#31-0114;

[0032] Figure 2 The luminescence spectrum of the sample prepared in Example 1 of the present disclosure before and after post-annealing;

[0033] Figure 3 The sample prepared in Example 1 of the present disclosure was annealed to obtain Eu2+ The decay curve of

[0034] Figure 4 The luminescence spectrum of the sample prepared in Example 2 of the present disclosure before and after post-annealing;

[0035] Figure 5 The sample prepared in Example 2 of the present disclosure was annealed to obtain Eu 2+ The decay curve of

[0036] Figure 6 The luminescence spectrum of the sample prepared in Example 3 of the present disclosure before and after post-annealing;

[0037] Figure 7 The sample prepared in Example 3 of the present disclosure was annealed to obtain Eu 2+ The decay curve of

[0038] Figure 8 The luminescence spectrum of the sample prepared in Example 4 of the present disclosure before and after post-annealing;

[0039] Fig. 9 The sample prepared in Example 4 of the present disclosure was annealed to obtain Eu 2+ The decay curve. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0041] The following will further illustrate a Eu 2+ Preparation method and properties of doped boroaluminate-based luminescent materials:

[0042] Embodiment 1:

[0043] According to the chemical Ba 2.97 Eu 0.03 GaAl3B4O 15 The stoichiometric ratio of each element in the mixture is as follows: 11.722 g of barium carbonate, 0.106 g of europium oxide, 1.874 g of gallium oxide, 3.060 g of aluminum oxide, and 4.947 g of boric acid. The weighed compounds are ground and mixed to obtain an initial mixture.

[0044] The mixture was pre-calcined for the first time in an air atmosphere at a temperature of 950°C for 3 hours. It was naturally cooled to room temperature and ground evenly;

[0045] The mixture pre-sintered for the first time was calcined for the second time in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, the calcination temperature was 950° C., the pre-calcination time was 5 hours, naturally cooled to room temperature, and ground evenly to obtain a precursor sintered compound.

[0046] The precursor sintered compound obtained in the above steps is post-annealed in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, and the temperature program is: from room temperature (room temperature refers to 10-30°C) to 750°C and sintered at this constant temperature for 5 hours, then heated to 950°C and sintered at this constant temperature for 3 hours, and finally heated to 1050°C and sintered at this constant temperature for 3 hours, and then cooled to room temperature in the furnace to obtain the final product of Example 1.

[0047] See attached Figure 1 , is a comparison of the X-ray powder diffraction pattern of the sample prepared according to this Example 1 with the standard card PDF#31-0114, and the result shows that the sample is a pure phase material.

[0048] See attached Figure 2 , is the luminescence spectrum of the sample prepared in Example 1 before and after post-annealing. It can be seen that the luminescence of the sample before post-annealing comes from Eu 3+ and Eu 2+ Two types of luminescence centers, Eu 3+ It is a characteristic sharp peak of luminescence, Eu 2+ It is a characteristic broadband band. After annealing, the residual Eu 3+ The luminescence is completely eliminated, and the chromaticity of the obtained cyan luminescence is pure;

[0049] Figure 3 The sample prepared in Example 1 was annealed to obtain Eu 2+ The decay curve shows that the luminescence lifetime is 0.147 microseconds, which is Eu 2+ The characteristic of the luminescent center is a fast luminescence lifetime.

[0050] Example 2

[0051] According to the chemical Ba 2.91 Eu 0.09 GaAl3B4O 15 The stoichiometric ratio of each element in the mixture is as follows: 9.188 g of barium carbonate, 0.253 g of europium oxide, 1.50 g of gallium oxide, 2.448 g of aluminum oxide, and 3.957 g of boric acid. The weighed compounds are ground and mixed to obtain an initial mixture.

[0052] The mixture was pre-calcined for the first time in an air atmosphere at a temperature of 500°C for 10 hours. It was naturally cooled to room temperature and ground evenly;

[0053] The mixture pre-sintered for the first time was calcined for the second time in a mixed gas of hydrogen and nitrogen with a volume ratio of 1:80, the calcination temperature was 1050°C, the pre-calcination time was 15 hours, naturally cooled to room temperature, and ground evenly to obtain a precursor sintering compound.

[0054] The precursor sintering compound obtained in the above steps is post-annealed in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, and the temperature program is: heating from room temperature to 550°C and maintaining the constant temperature for sintering for 3 hours, then heating to 750°C and maintaining the constant temperature for sintering for 3 hours, and finally heating to 950°C and maintaining the constant temperature for sintering for 8 hours, and cooling to room temperature with the furnace to obtain the final product of Example 2.

[0055] See attached Figure 1 , is a comparison of the X-ray powder diffraction pattern of the sample prepared according to this Example 1 with the standard card PDF#31-0114, and the result shows that the sample is a pure phase material.

[0056] See attached Figure 4 , is the luminescence spectrum of the sample prepared in Example 2 before and after post-annealing. It can be seen that the luminescence of the sample before post-annealing comes from Eu 3+ and Eu 2+ Two types of luminescence centers, Eu 3+ It is a characteristic sharp peak of luminescence, Eu 2+ It is a characteristic broadband band. After annealing, the residual Eu 3+ The luminescence is completely eliminated, and the chromaticity of the obtained cyan luminescence is pure;

[0057] Figure 5 The sample prepared in Example 2 was annealed to obtain Eu 2+ The decay curve of the luminescence lifetime is 0.131 microseconds, which is Eu 2+ The characteristic of the luminescent center is a fast luminescence lifetime.

[0058] Example 3

[0059] According to the chemical Ba 2.85 Eu 0.15 GaAl3B4O 15 The stoichiometric ratios of the elements in the solution are weighed separately:

[0060] 6.99 g of barium oxide, 0.422 g of europium oxide, 1.499 g of gallium oxide, 3.744 g of aluminum hydroxide, and 2.229 g of boron trioxide. The weighed compounds were ground and mixed to obtain an initial mixture.

[0061] The mixture was pre-calcined for the first time in air atmosphere at a temperature of 500°C for 5 hours. It was naturally cooled to room temperature and ground evenly;

[0062] The mixture pre-sintered for the first time was calcined for the second time in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, the calcination temperature was 950° C., the pre-calcination time was 8 hours, naturally cooled to room temperature, and ground evenly to obtain a precursor sintered compound.

[0063] The precursor sintered compound obtained in the above steps is post-annealed in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, and the temperature program is: heating from room temperature to 750°C and maintaining the constant temperature for sintering for 5 hours, then heating to 850°C and maintaining the constant temperature for sintering for 5 hours, and finally heating to 950°C and maintaining the constant temperature for sintering for 6 hours, and cooling to room temperature in the furnace to obtain the final product of Example 4.

[0064] See attached Figure 1 , is a comparison of the X-ray powder diffraction pattern of the sample prepared according to Example 3 with the standard card PDF#31-0114, and the result shows that the sample is a pure phase material.

[0065] See attached Figure 6 , is the luminescence spectrum of the sample prepared in Example 3 before and after post-annealing. It can be seen that the luminescence of the sample before post-annealing comes from Eu 3+ and Eu 2+ Two types of luminescence centers, Eu 3+ It is a characteristic sharp peak of luminescence, Eu 2+ It is a characteristic broadband band. After annealing, the residual Eu 3+ The luminescence is completely eliminated, and the chromaticity of the obtained cyan luminescence is pure;

[0066] Figure 7 The sample prepared in Example 3 was annealed to obtain Eu 2+ The decay curve of the luminescence lifetime is 0.117 microseconds, which is Eu 2+ The characteristic of the luminescent center is a fast luminescence lifetime.

[0067] Example 4

[0068] According to the chemical Ba 2.79 Eu 0.21 GaAl3B4O 15 The stoichiometric ratios of the elements in the solution are weighed separately:

[0069] 7.157 g of barium carbonate, 0.480 g of europium oxide, 1.218 g of gallium oxide, 1.989 g of aluminum oxide, and 3.215 g of boric acid. The weighed compounds were ground and mixed to obtain an initial mixture.

[0070] The mixture was pre-calcined for the first time in an air atmosphere at a temperature of 800°C for 5 hours. It was naturally cooled to room temperature and ground evenly;

[0071] The mixture pre-sintered for the first time was calcined for the second time in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, the calcination temperature was 950° C., the pre-calcination time was 8 hours, naturally cooled to room temperature, and ground evenly to obtain a precursor sintered compound.

[0072] The precursor sintered compound obtained in the above steps is post-annealed in a mixed gas with a volume ratio of hydrogen to nitrogen of 1:80, and the temperature program is: heating from room temperature to 750°C and maintaining the constant temperature for sintering for 5 hours, then heating to 850°C and maintaining the constant temperature for sintering for 5 hours, and finally heating to 950°C and maintaining the constant temperature for sintering for 6 hours, and cooling to room temperature in the furnace to obtain the final product of Example 4.

[0073] See attached Figure 1 , is a comparison of the X-ray powder diffraction pattern of the sample prepared according to Example 4 with the standard card PDF#31-0114, and the result shows that the sample is a pure phase material.

[0074] See attached Figure 8 , is the luminescence spectrum of the sample prepared in Example 4 before and after post-annealing. It can be seen that the luminescence of the sample before post-annealing comes from Eu 3+ and Eu 2+ Two types of luminescence centers, Eu 3+ It is a characteristic sharp peak of luminescence, Eu 2+ It is a characteristic broadband band. After annealing, the residual Eu 3+ The luminescence is completely eliminated, and the chromaticity of the obtained cyan luminescence is pure;

[0075] Fig. 9 The sample prepared in Example 4 was annealed to obtain Eu 2+ The decay curve of the luminescence lifetime is 0.095 microseconds, which is Eu 2+ The characteristic of the luminescent center is a fast luminescence lifetime.

[0076] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. Eu 2+ A doped boroaluminate-based luminescent material, characterized in that The chemical formula of the luminescent material is Ba3GaAl3B4O 15 :3xEu 2+ , x is Eu 2+ Replace Ba 2+ Ion mole number, and 0.01≤x≤0.07, unsubstituted Ba in the chemical formula 2+ and Eu 2+ The total number of moles is 3.

2. Eu according to claim 1 2+ A doped boroaluminate-based luminescent material, characterized in that The luminescent material can emit cyan light of 515-525 nanometers under the excitation of light in the ultraviolet-near ultraviolet band.

3. Preparation of Eu as claimed in claim 1 2+ Method for doping boroaluminate-based luminescent materials, characterized in that The steps include: Step (1): According to the chemical formula Ba3GaAl3B4O 15 :3xEu 2+ (x is Eu 2+ Replace Ba 2+ ion mole number, 0.01≤x≤0.07), weighing respectively: a compound containing barium ions, a compound containing gallium ions, a compound containing aluminum ions, a compound containing boron ions, and a compound containing europium ions, grinding and mixing the weighed compounds to obtain an initial mixture; The mixture is pre-calcined for the first time in an air atmosphere at a temperature of 500°C to 950°C for 3 to 10 hours; cooled naturally to room temperature, and ground evenly; The mixture pre-sintered for the first time is calcined for the second time in a reducing atmosphere at a calcination temperature of 950°C to 1050°C for a pre-calcination time of 5 to 15 hours, cooled naturally to room temperature, and ground evenly to obtain a precursor sintered compound. Step (2): The precursor sintered compound obtained in step (1) is subjected to post-annealing treatment in a reducing atmosphere, the temperature is gradually increased in stages and maintained for a certain period of time, and then cooled to room temperature to obtain Eu 2+ Doped boroaluminate-based luminescent material; the stepwise heating refers to a temperature of 400-1200° C., and the maintaining time refers to 0.5-24 hours.

4. The preparation method according to claim 3, characterized in that: The compound containing barium ions is: one of barium oxide and barium carbonate; And / or, the gallium-containing ion Ga 3+ The compound is gallium oxide; And / or, the compound containing aluminum ions is one of aluminum oxide and aluminum hydroxide; And / or, the compound containing boron ions is one of boron trioxide and boric acid. And / or, the compound containing europium ions is europium oxide.

5. The preparation method according to claim 3, characterized in that: The reducing atmosphere is one of the following three atmospheres, or any combination thereof: (1) Hydrogen, or a mixture of hydrogen and nitrogen in a volume ratio of 1:0.2 to 85; (2) Carbon monoxide gas; (3) Gas produced by the combustion of carbon particles or various activated carbons in air.

6. The preparation method according to claim 3, characterized in that: In the post-annealing procedure in step (2), the annealing in a reducing atmosphere requires at least two stages with different temperatures and is completed continuously in a single procedure.

7. The preparation method according to claim 3, characterized in that: In the post-annealing procedure in step (2), the annealing is set in a reducing atmosphere, firstly the temperature is raised from room temperature to 550-750°C and kept at the constant temperature for 3-5 hours, then the temperature is raised to 750-950°C and kept at the constant temperature for 3-8 hours, and finally the temperature is raised to 950-1050°C and kept at the constant temperature for 3-8 hours, and then the final product Eu is obtained by cooling to room temperature with the furnace. 2+ Doped boroaluminate-based luminescent materials.

8. Eu according to claim 1 2+ A doped boroaluminate-based luminescent material, characterized in that The luminescent material is applied to luminescent and display devices based on ultraviolet and near-ultraviolet light excitation.